The perception of consumers toward content creators and their impact on consumer purchase decisions - Alce, John Bernard M. Belmonte, Faola Nixon C. Briones, Mikaella Marie E. Galope, Ianne Aierra F. Peralta, Erilyn Diane C. Salonga, Zyra B. Santos, Faith M. Serrano, Alfred Bon A. Suganob, Ahyanna Jean E. 4 0 16; 5
ABSTRACT This research aims to explore the impact of perception of consumers towards content creators and their impact on consumer purchase decisions. The study uses a quantitative research design to gather data from social media users who have experienced engaging with content economy services. Findings revealed that there is a significant relationship between the number of hours watching videos and the amount purchased by consumers. Furthermore, the study revealed some factors a content creator may focus on to gain more engagement on their content. As researchers explore how consumer's perception on content creators (like preferences on how content creators deliver their videos) affects what people choose to buy. It focuses on the Theory of Planned Behavior (TPB), which explores the constructs of attitude, subjective norm, and perceived behavioral control shape consumers' intentions to purchase after engaging with content. Researchers examine how content creators can influence these TPB factors through their content characteristics. By understanding the interplay between content and consumer plychology, this research aims to contribute knowledge in constructing marketing strategies for content creators and platforms.
Business Research: (BSBA major in Marketing Management) - Pamantasan ng Lungsod ng Maynila, 2024
Keywords: 2 -- 0; 6; 20; 20; 2